Literature across generations; The Old Javanese epic poem "Bhāratayuddha" translated into Modern Javanese - Kamiishi, Keiko (Wacana, Journal of the Humanities of Indonesia, 2025)
In the eighteenth and nineteenth centuries, a revival movement of classical Javanese (Kawi) literature arose in the royal courts of south Central Java. As part of this revival, Old Javanese literary works were rewritten in Modern Javanese, giving Javanese people at that time renewed access to their literary heritage. The paper deals with a specific manuscript, Add MS 12279 in the British Library, which contains Modern Javanese word-for-word and line-for-line “translations” inserted between lines of the Old Javanese epic poem Bhāratayuddha. The unique structure of the manuscript reveals the translation strategies used to address the challenges of balancing the transmission of meaning with the modernization of language. Exploring the interpretation of the Old Javanese work in modern Java sheds light on the entwinement of the different languages (Old Javanese and Modern Javanese), different religions (Hindu and Islam), and different times (ancient and modern).